Probability, statistics and stochastic processes - Seksan Kiatsupaibul ([Bangkok, Thailand] : Chulalongkorn University Press, 2021)
This book is divided into three parts; part I Probability Part II Statistics and Part III Stochastic processes, the discussion rangs from basic concepts such as conditional probability and independence to more advanced concepts such as limit theorems and stochastic processes. Some research topics such as the rapid mixing property of reversible markov chains are also discussed. In this way, the reader can successfully bulid a bridge from these basic statitical ideas to more advanced applications and research topics.
Keywords: Probabilities; Mathematical statistics; Stochastic processes